Resilience and familism : the dynamic nature of families in the Philippines - Gregorio, Veronica L.; Batan, Clarence M.; Blair, Sampson Lee (Emerald Publishing Limited, 2023)
Recognising the distinctive context of the Philippines, with its unique long history, and peculiar population distribution across thousands of islands, this edited collection analyses its decidedly familial culture. Why do Filipino families maintain perhaps the strongest family bonds of any culture? How have shown a unique ability to persevere, even when faced with the direst of circumstances? Covering a broad range of topics, chapters and commentaries delve into changing gender roles, poverty and family dynamics, mothering in prison, teenage fatherhood, dating and mate selection, rural family norms, the interweave of family and community, media representations on families, new forms of parenthood, remittances and familial support systems, and how overseas employment affects spousal and parent-child relationships. A highly comprehensive ethnographic analysis, Resilience and Familism demonstrates in a specifically Filipino context how strong familial ties can affect inner strength and outer determination.
Keywords: Families -- Philippines.; Resilience (Personality trait); Family & Relationships -- General.; Sociology: family & relationships.; elektronické knihy; electronic books